Venomous Spiders of the Southeastern US: An Unexpected Threat - Alex Collins; Oreta Samples (Georgia Southern University, 2015)
Background: Environmental health specialists recommend that residents of the Southeastern US, including Georgia, have the ability to identify the three venomous spiders indigenous to this area. It is necessary to recognize the black widow, brown widow, and brown recluse spiders and to be familiar with the likely habitats of these insects and with the symptoms of bites. The primary author, who serves as an Environmental Health Specialist and is a hobbyist who works with distressed wood, frequently encounters all three of these spiders. Methods: A literature review supports the fact that these three venomous spiders are indigenous to Georgia. Results: Spiders, a common sight in rural and urban areas of Georgia, are often not considered as being especially dangerous. Three common species of spiders found in Georgia are, however, venomous. Conclusions: Recognition of spiders is particularly appropriate for the protection of food service workers, employees working in tourist accommodations, and hobbyists who routinely invade spider habitats. The evaluation of educational efforts may be assessed by the numbers of reported cases of spider bites among these populations.